2005
DOI: 10.1302/0301-620x.87b4.14954
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclide imaging of the painful hip arthroplasty

Abstract: Two major complications of hip replacement are loosening and infection. Reliable differentiation between these pathological processes is difficult since both may be accompanied by similar symptoms. Our aim was to assess the diagnostic ability of triple-phase bone scanning (TPBS) and positron-emission tomography (PET) to detect and differentiate these complications in patients with a hip arthroplasty. Both TPBS and PET were performed in 63 patients (92 prostheses). The radiotracer for PET imaging was (18)F-fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(33 citation statements)
references
References 27 publications
1
31
0
1
Order By: Relevance
“…Increased uptake in the neck of the prosthesis, accompanied by uptake around the whole cup of the prosthesis and/or around the whole shaft, fits with aseptic prosthetic loosening. Finally, infection is characterised by increased uptake in all the abovementioned prosthesis-bone interfaces -including periprosthetic soft tissues (Reinartz et al, 2005). Nevertheless, these criteria have not been accepted by all, and are also criticised.…”
Section: Interpretation Criteriamentioning
confidence: 99%
“…Increased uptake in the neck of the prosthesis, accompanied by uptake around the whole cup of the prosthesis and/or around the whole shaft, fits with aseptic prosthetic loosening. Finally, infection is characterised by increased uptake in all the abovementioned prosthesis-bone interfaces -including periprosthetic soft tissues (Reinartz et al, 2005). Nevertheless, these criteria have not been accepted by all, and are also criticised.…”
Section: Interpretation Criteriamentioning
confidence: 99%
“…Vanquickenborne and colleagues [43] interpreted PET images to represent infection when FDG uptake around the prosthesis is two scores higher than that in the contralateral distal femur. In contrast, Reinartz and his coworkers [10,50] considered infection as the diagnosis when increased FDG activity in the periprosthetic soft tissue and arthroplasty interface was observed. Our group [49,51] has used similar criteria for infection as those of Reinartz and his coworkers [10,50].…”
Section: Coincident Cameramentioning
confidence: 99%
“…Most infections cannot be diagnosed accurately by bone and gallium scans, however [9]. Although three-phase bone scintigraphy has been used in the evaluation of painful prosthesis replacement, it lacks adequate accuracy [10]. Indium 111-labeled leukocyte scintigraphy, when combined with technetium (Tc)-99m-sulfur colloid bone marrow imaging, may provide reasonable accuracy for the detection of infection after arthroplasty [11][12][13][14].…”
Section: Coincident Cameramentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy of detecting infection in a knee prosthesis reported by Zhuang et al [47] was quite low at 77.8%. When it comes to infection following hip arthroplasty, the accuracy ranges between 89-95% [47][48][49]. On the other hand, studies have shown contradictory results when it comes to 18 F-FDG-PET-(CT) in prosthetic joint infection.…”
Section: Originalmentioning
confidence: 99%